Working with agile and crowd: human factors identified from the industry - Qayyum, Shamaila; Imtiaz, Salma; Hayat Khan, Huma; Almadhor, Ahmad; Karovic, Vincent (Frontiers in Computer Science, 2024)
Crowd Source Software Development (CSSD) is an emerging technique in software development. It helps utilize the diversified skills of people from across the world. Like all emerging techniques CSSD has its own benefits and challenges. Some unique challenges arise when CSSD is used with Agile methodology. This is because many characteristics of CSSD differ from Agile principles. CSSD is a distributed approach where workers are unknown to each other whereas Agile advocates team-ness and is mostly suitable for co-located teams. Many organizations are now combining Continuous Software Development (CSSD) and Agile methodologies, yet there's limited understanding of the implications of this integration. It's crucial to emphasize the human factors at play when implementing Agile alongside CSSD. This involves considering how teams interact, communicate, and adapt within these frameworks. By recognizing these dynamics, organizations can better navigate the complexities of integrating CSSD and Agile, ultimately fostering more efficient and collaborative development processes. This study aims to explore the human factors involved in the integration of CSSD with Agile, by identifying the challenges that practitioners face when they follow Agile with CSSD and the strategies they follow. The study contributes by providing an in-depth understanding of a new approach, CSSD, integrated with Agile. The study also explores the challenges from practitioners that are not already enlisted. These identified challenges are grouped into 6 different categories, which are: trust-related challenges, coordination and communication challenges, organizational challenges, taskrelated challenges, project-related challenges, and some general challenges. Strategies for each of these categories of challenges are also identified. The list of challenges and strategies identified in this study can be helpful in further research of CSSD and Agile integration. The practitioners can also follow these strategies to reduce the impact of challenges they face while they perform CSSD along with Agile.